The Relationship Between Practical Experience in Teaching Skills and Self-Confidence in Becoming a Culinary Teacher - Raditiya Putri Setyo Maharani; Mariani Mariani; Yeni Yulianti (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study aims to examine the correlation between Teaching Skills Practice (PKM) experience and self-confidence in becoming a culinary teacher. The research was conducted from May to December 2025 with a population consisting of students from the 2020 and 2021 cohorts of the Culinary Education Study Program at Universitas Negeri Jakarta. The study employed a quantitative method with a correlational approach. The sampling technique used was purposive sampling, involving a total of 89 respondents. The data were analyzed using descriptive analysis, product moment correlation, the coefficient of determination, and significance testing. The findings indicate that the correlation between teaching skills practice experience and self-confidence falls into the moderate category. The Pearson correlation analysis shows a correlation value of 0.540, with an F-statistic of 35.7, which is greater than the critical value of 3.96. This result suggests a positive and moderately strong significant relationship between teaching skills practice experience and self-confidence. Furthermore, teaching skills practice experience contributes 29.1% to students’ self-confidence in becoming culinary teachers